2018
DOI: 10.1051/matecconf/201819303050
|View full text |Cite
|
Sign up to set email alerts
|

Model and mechanism of carbon nanotube stabilization with plasticizer

Abstract: Abstract. Mechanism of stabilization of carbon nanotube (CNT) water suspension with plasticizer based on sulfated naphthalene formaldehyde resins is proposed in this article. CNT stabilization is achieved at the expense of fixing plasticizer group on the nanoparticle surface. Nonpolar part of plasticizer provides the formation of high-viscosity streak between CNTs particles and dispersion medium, and polar part provides the formation of double electrical layer, that supports formation of CNT micelle. Model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The tap water (pH = 7.6) and the tap water with polycarboxylate resin ester superplasticizer have been used as the disperse phases; their general formula is: (2) UBFGS suspensions have been prepared using the mechanical stirring by magnetic mixer for 5 min. Ready-to-use ultradisperse slag suspensions with the corresponding concentrations have been poured into the 100 cm 3 cylinders in order to observe the sedimentation, while the time period from the suspension preparation beginning to the particles intensive sedimentation completion, disperse phase clarification completion, and reaching absolutely clear disperse phase have been measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tap water (pH = 7.6) and the tap water with polycarboxylate resin ester superplasticizer have been used as the disperse phases; their general formula is: (2) UBFGS suspensions have been prepared using the mechanical stirring by magnetic mixer for 5 min. Ready-to-use ultradisperse slag suspensions with the corresponding concentrations have been poured into the 100 cm 3 cylinders in order to observe the sedimentation, while the time period from the suspension preparation beginning to the particles intensive sedimentation completion, disperse phase clarification completion, and reaching absolutely clear disperse phase have been measured.…”
Section: Methodsmentioning
confidence: 99%
“…The studies of the cement stone containing the carbon nanotubes (CNT) stabilized suspension obtained by acoustic cavitation method demonstrate high performance [1][2][3][4], which allows to consider the CNT concentrate as one of the components for the mortar preparation in structural and thermally insulated aerated concrete production.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have not only unique technical characteristics, but are also interesting from the standpoint of chemistry and physical chemistry. This is due to the ability of CNTs to attach a variety of radicals to their surface, which can serve as catalytic centers or nuclei for various chemical transformations [8]. It has been experimentally shown [9,10] that during the oxidation of CNTs, their surface is covered with hydrocarbon radicals: -СООН, -СО, -СОН.…”
Section: Introductionmentioning
confidence: 99%
“…However, a negative point is also possible associated with the agglomeration of functionalized CNTs in the spaces between large cement particles. It causes deterioration of mechanical properties [8,11]. Agglomeration of CNTs can be minimized if they are dispersed by various methods [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure uniform distribution of slag particles in the volume of the cement matrix, it is proposed to introduce FGS as a suspension into the cement instead of mixing water [16][17][18]. The papers [19][20][21][22][23][24][25] carried out studies on the establishment of aggregative and sedimentation stability of dispersions of various substances of the nanoscale series: carbon nanotubes, europium oxohydroxide hydrosol, γ-Al2O3 sol, etc. The results of the studies showed that the establishment of aggregative and sedimentation stability of dispersions and the use of methods of homogenization and stabilization contribute to the uniform distribution of particles in the volume of the cement matrix and the production of products with enhanced performance properties.…”
Section: Introductionmentioning
confidence: 99%